Techno-Economic Evaluation of Novel Hybrid Biomass and Electricity-Based Ethanol Fuel Production - Melin, Kristian; Nieminen, Harri; Klüh, Daniel; Laari, Arto; Koiranen, Tuomas; Gaderer, Matthias (Frontiers in Energy Research, 2022)
In order to limit climate change, fast greenhouse gas reductions are required already before 2030. Ethanol commonly produced by fermentation of sugars derived either from starch-based raw material such as corn, or lignocellulosic biomass is an established fuel decarbonizing the transport sector. We present a novel selective and flexible process concept for the production of ethanol with electricity and lignocellulosic biomass as main inputs. The process consists of several consecutive steps. First synthesis gas from gasification of biomass is purified by filtration and reforming and fed to methanol synthesis. The produced methanol is fed to acetic acid synthesis, together with a carbon monoxide-rich stream separated from the synthesis gas by membranes. Finally, acetic acid is hydrogenated to yield ethanol. With the exception of acetic acid hydrogenation, the overall process consists of technically mature subprocesses. Each process step was modelled in Aspen Plus to generate the mass and energy balances for the overall process. Additionally, the CO2 emissions and economic feasibility were assessed. Three separate cases were investigated. In the first two cases, the syngas carbon (CO and CO2) was split between methanol and acetic acid synthesis. The cases included either allothermal (case A) or electrically heated reforming (case B). In case C, maximum amount of CO was sent to acetic acid synthesis to maximize the acetic acid output, requiring a small additional carbon dioxide input to methanol synthesis. In all cases, additional hydrogen to methanol synthesis was provided by water electrolysis. Each case was designed at biomass input of 27.9 MW and the electrolyzer electricity requirement between 36 and 43.5 MW, depending on the case. The overall energy efficiency was calculated at 53–57%, and carbon efficiencies were above 90%. The lowest levelized cost of ethanol was 0.65 €/l, at biomass cost of 20 €/MWh and electricity cost of 45 €/MWh and production scale of approximately 42 kt ethanol per year. The levelized cost is competitive with the current biological route for lignocellulosic ethanol production. The ethanol price is very sensitive to the electricity cost, varying from 0.56 to 0.74 €/l at ±30% variation in electricity cost.